Psychological Features of Teaching Adolescents in the Process of Education - Abduvakhobova Dildora Erkinovna (Periodica Journal, 2022)
This article discusses the issue of raising and educating a teenager, taking into account his age-related psychological characteristics, the issue of mutual understanding between parents and children, the issue of the relationship of a teenager with peers, taking into account family circumstances, the reasons that cause moral problems of situational circumstances are considered. And also opinions are given on the correct construction of the relationship of a teenager with friends.
Keywords: teenager; self-portrait; relationship; family